A study on pulmonary manifestations in patients with malaria from northwestern India (Bikaner) - K.C. Nayak, Mohini, S. Kumar, R.S. Tanwar, V. Kulkarni, A. Gupta, P. Sharma, P. Sirohi & P. Ratan (Journal of Vector Borne Diseases, 2011)
Background & objectives: Plasmodium falciparum (Pf) and Plasmodium vivax (Pv) are responsible for most ofthe global burden of malaria. With changing spectrum of clinical presentation in malaria, pulmonary systeminvolvement has always been under diagnosed. The present study was planned to estimate the pulmonary systeminvolvement in patients with malaria from north-western India (Bikaner).Study design & description of the patients: Our study was conducted during 2007 to 2009 in 200 cases of severemalaria [Pf , Pv, and mixed (Pf + Pv)] with pulmonary involvement. It included adult patients of both sexes (145males and 55 females) belonging to all age groups. The diagnosis of Pf and Pv was confirmed by demonstratingasexual form of parasites in peripheral blood smear and OptiMal test.Main outcome measures: Pulmonary involvement was observed in 30% (60/200) patients among which cough in24% , dyspnea in 12%, acute respiratory distress syndrome (ARDS) in 7% , bronchitis in 3% and pneumonia in1.5% were the major clinical manifestations of malaria. Metabolic acidosis and low oxygen saturation wasobserved in 7% patients. Chest X-ray abnormality in 11.5% patients, 7% had bilateral infiltrates, 1.5% hadinflammatory patch and 3% had findings suggestive of bronchitis. Spirometry findings showed 17% patientshad early small airway obstruction. All the patients with ARDS had poor disease outcome.Results & conclusion: Our results suggest that pulmonary system involvement was observed in patients infectedwith Pf and Pv. If these clinical presentations are ignored, it may lead to delay in diagnosis and can alter theoutcome and prognosis of the disease. Therefore, early diagnosis of malaria induced ARDS can significantlyaffect the outcome.